1984
DOI: 10.1111/j.1471-4159.1984.tb05405.x
|View full text |Cite
|
Sign up to set email alerts
|

Chloride Ions Preferentially Mask High‐Affinity GABA Binding Sites

Abstract: Chloride ions (Cl-) act to regulate the appearance of gamma-aminobutyric acid (GABA) binding sites in synaptic membranes from bovine retinas. Scatchard analysis indicates that the presence of Cl- results in a preferential decrease (85%) in the number of high-affinity binding sites, with no statistically significant change in the affinity (KD) of either the high- or low-affinity sites. The finding that the appearance of this binding site is altered by the presence of Cl- may indicate that Cl- acts, either direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1986
1986
1990
1990

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The general validity of this view has been challenged by the recent report that thiocyanate could not enhance the [3H]GABA displacing potency of the new pyridazinyl-GABA antagonists (Heaulme et al, 1986). Chloride ions have also been shown to remove the high-affinity GABA binding sites (Madtes, 1984) and induce shifts in the displacing potencies of GABA agonists and antagonists similarly to thiocyanate (Olsen and Snowman, 1983). Therefore these effects of C1-and SCNhave been considered as common properties of Eccles anions penetrating through the attached chloride channel (Olsen and Snowman, 1983).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The general validity of this view has been challenged by the recent report that thiocyanate could not enhance the [3H]GABA displacing potency of the new pyridazinyl-GABA antagonists (Heaulme et al, 1986). Chloride ions have also been shown to remove the high-affinity GABA binding sites (Madtes, 1984) and induce shifts in the displacing potencies of GABA agonists and antagonists similarly to thiocyanate (Olsen and Snowman, 1983). Therefore these effects of C1-and SCNhave been considered as common properties of Eccles anions penetrating through the attached chloride channel (Olsen and Snowman, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…1984a), the displacing potency of SR 95 103 was significantly decreased ( Table 1). In contrast, the presence of C1ions, which reduces the number of high-affinity GABA sites (Madtes, 1984), shifted the displacing potency of SR 95103 in the opposite direction (Table 1).…”
Section: H]gaba Bindingmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we did not find a Ca2' effect on our GABAA binding when the Ca2' concentrations were lower than 1 mM, while Majewska and Chuang (20) indicate that Ca2' is necessary for hgh-affinity GABAA sites in the brain. Thus, it is possible that these high-affinity GABAA sites could be absent from adrenal medulla or that they could be masked by C1-ions in the medium, as was reported for brain (21) (notice that we used Tris-HCl buffer).…”
Section: Binding Site Saturation Analysismentioning
confidence: 90%
“…Kardos et al (1 985) have studied the characteristics of GABA binding to cells grown in culture using a physiological incubation medium, and Yang and 01-sen ( 1987) recently have studied the effect of incubation temperature on the binding of muscimol to membranes prepared from mouse brain. Several studies on the effects of Na+ and C1-on GABAA receptor binding have been reported (Enna and Snyder, 1977;Hitzemann and Loh, 1978;Kurioka et al, 1981;Madtes, 1984), but these studies in general were performed at low temperatures, and predated the discovery of the GABAs receptor and the availability of compounds that selectively bind to each receptor type or the transport site.…”
mentioning
confidence: 99%